PENGARUH UMUR PANEN YANG BERBEDA TERHADAP PRODUKSI DAN KANDUNGAN BAHAN KERING SERTA PROTEIN KASAR SORGHUM GREEN FODDER HYDROPONIC - Sri Widiastuti; Tri Puji Rahayu; Mohamad Haris Septian (Jurnal Ilmu dan Teknologi Peternakan, 2021)
Hydroponics is a forage cultivation technique that is suitable to be applied to overcome the constraints of climate dependence and land availability. Forage that is cultivated hydroponically is often called green fodder hydroponic. Sorghum is a plant that has the potential to be developed as a hydroponic green fodder because it grows well in tropical environments and is efficient in producing photosynthetic products. This study aims to determine the content and production of Dry Matter (DM) and Crude Protein (CP) sorghum green fodder hydroponic. The study was conducted experimentally with a completely randomized design. The collected data were analyzed using Duncan's Test. The treatments were harvesting ages of 7 days, 10 days and 13 days, then measured the production of fresh ingredients, DM content, DM production, CP content, and CP production. The results showed that the longer the age of harvest significantly (p>0.05) increased the content of DM and CP but significantly (p>0.05) decreased the production of fresh ingredients and the production of DM The results of CP production showed that the longer the age of harvest was not significant (p<0.05). In conclusion, the long harvesting age of hydroponic sorghum green fodder causes an increase in the content of DM and CP, but decreases the production of fresh ingredients and the production of DM